2020
DOI: 10.1371/journal.pone.0244588
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the effectiveness of group-based exercise to other non-pharmacological interventions for chronic low back pain: A systematic review

Abstract: Background Low back pain (LBP) is the leading cause of disability worldwide with a substantial financial burden on individuals and health care systems. To address this, clinical practice guidelines often recommend non-pharmacological, non-invasive management approaches. One management approach that has been recommended and widely implemented for chronic LBP is group-based exercise programs, however, their clinical value compared with other non-pharmacological interventions has not been investigated systematica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…Finally, our study corroborates the systematic review conducted by Lemieux et al ( 40 ), which found no statistically significant differences in disability, quality of life, and pain between exercise and other non-pharmacological interventions in patients with CNLBP. Therefore, to date, exercise programs are sufficient to control this dysfunction.…”
Section: Discussionsupporting
confidence: 92%
“…Finally, our study corroborates the systematic review conducted by Lemieux et al ( 40 ), which found no statistically significant differences in disability, quality of life, and pain between exercise and other non-pharmacological interventions in patients with CNLBP. Therefore, to date, exercise programs are sufficient to control this dysfunction.…”
Section: Discussionsupporting
confidence: 92%
“…Rather than perpetuating a recurring trend of substituting psychotropics, we should work to reduce the overall use of psychotropic medications by implementing safer non‐pharmacologic approaches. In the case of chronic pain, there is good evidence for exercise and psychoeducational interventions, though it is limited in patients living with dementia 22 . In the case of BPSD, systematic reviews of non‐pharmacologic interventions such as caregiver and health care worker training in person‐centered care and dementia communication skills show significant reductions in behavioral symptoms, with effect sizes that are small but greater than for antipsychotics 23,24 …”
Section: Figurementioning
confidence: 99%
“…In the case of chronic pain, there is good evidence for exercise and psychoeducational interventions, though it is limited in patients living with dementia. 22 In the case of BPSD, systematic reviews of non-pharmacologic interventions such as caregiver and health care worker training in personcentered care and dementia communication skills show significant reductions in behavioral symptoms, with effect sizes that are small but greater than for antipsychotics. 23,24 Ultimately, prescribers trying to manage complex symptoms and relieve distress among older adults living with dementia are working in an area devoid of good evidence where there are constantly trade-offs.…”
mentioning
confidence: 99%
“…49 When educating patients is a goal, research indicates that the most effective health promotional programmes for adults are social and educational group activities rather than individual health-focused interventions. 50,51 Educational group actions can help improve aspects such as differences in coping strategies illness perceptions, self-efficacy, fearavoidant beliefs, locus of control, and pain attitudes in different populations. However, when these actions are carried out, ethnic and cultural patient characteristics should be considered because these affect the pain beliefs, cognitions, and behaviours in those with chronic pain.…”
Section: Educate the Patients And Involve Them In Pain Managementmentioning
confidence: 99%